Проект "Герои народа - герои страны" - Воронцов Владимир Степанович (Монпоражён, 2019)
Экземпляры: ф.10 (20200831) / Инвентарный номер: 60163 / Цена: / Сис.шифр: 63.3(2Рос.Удм)6 / Авт.знак: П 79 / ГРНТИ: 03.23.55 / ББК: 63.3(2)622,88